Isometric beak morphology in Phoenicopterus ruber roseus, Phoenicopteriformes - Parés-Casanova, Pere M.; Arcas, Sandra (Acta Biologica Szegediensis, 2019)
It is well documented that size of various body parts tends to correlate within the same individual. In the current study, we explore the relationship between body weight and some area and lineal beak measurements in a sample of 17 corpses of Greater flamingo Phoenicopterus ruber roseus (10 immatures and 7 adults), collected and after obtaining beak radiographic latero-lateral projections. On images, the following traits were obtained: area of rhinotheca -the sheath covering the maxilla- and gnathotheca -the sheath covering the mandibular-, rhamphotheca height, ocular area, ocular height, ocular width, height, width and area of nares. Our results suggest that some beak measurements are positively correlated with body weight, while nostril area is not. Specifically, rhinotheca and gnathotheca areas and rhamphotheca height were strongly coupled and largely correlated to body weight. The observed differences in beak dimensions are merely a consequence of body weight difference. It is suggested, that the cranial skeleton and musculature are closely linked at least developmentally, allowing for efficient functional integration, but genetic and functional tests must have been performed to reveal the exact nature of the flamingo beak change.